Beliefs and the dead in Reformation England - Marshall, Peter, 1964 Oct. 26- (Oxford University Press, 2002)
This text examines conflicting 16th-century attitudes to the doctrine of purgatory, as well as the religious culture surrounding them which underscored the fabric of society. It charts the Protestant authorities' attempts to stamp out the rituals and provide replacements.